The influence of inventory management practice on operation efficiency: A case study of Muehlbauer Automation (Malaysia) Sdn. Bhd. Melaka - Sundra Sagar, Sritharan (2024)
Studies have been conducted on the influence of inventory management practice on operation efficiency: a case study of Muehlbauer Automation (Malaysia) Sdn. Bhd., Melaka. Manufacturing company like Muehlbauer Automation are perceived to be failing due to ineffective management practices, using an interview survey, this study pursued to determine the inventory-management practices of Muehlbauer Automation operating in Ayer Keroh, Melaka, and to evaluate the effectiveness of the inventorymanagement practices currently used by these company. In addition, the study also to determine the challenges, if any, those are experienced by Muehlbauer Automation from the inventory- management practices currently used. This study was motivated by a lack of research on inventory-management practices Muehlbauer Automation. The findings of the study revealed that most of the Muehlbauer Automation used. Rule of Thumb‟ as an inventory-management practice. Regarding the effectiveness of the practices used, the study revealed that the Muehlbauer Automation investigated were perceived to be moderately effective, with Muehlbauer Automation practising good inventory management techniques such as Enterprise Resources Planning (ERP). Muehlbauer Automation faced a number of challenges from its current inventorymanagement practices. The findings from the respondents indicated that some of the main challenges included surplus, shortage of inventory, data entry errors, and slow moving parts that had been increasing due to incompetent staff; other challenges included physical inventory that did not match records; and an inability to meet customer demand.This study closes the knowledge gap in this underutilised field of research and adds to the body of literature on Muehlbauer Automation's inventorymanagement procedures.The results of this study will be helpful to Muehlbauer Automation's decision-makers as they will advance various inventory-management techniques and best practices that are necessary for firms to thrive.